2018
DOI: 10.1002/cctc.201701866
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Homogeneous and Heterogeneous Coupling of Furfural with Biomass‐Derived Alcohols

Abstract: The tandem dehydrogenation and aldol condensation of butanol with furfural was investigated over homogeneous and heterogeneous catalysts using kinetics and isotope effects. In the homogeneous system, Ni(dppe)Cl2 catalyzes the transfer dehydrogenation of butanol to the furfural, whereas the aldol condensation of butyraldehyde and furfural takes place over the basic K2CO3 cocatalyst. In the heterogeneous system, a transition‐metal‐free mixed Mg–Al oxide, both the transfer hydrogenation and aldol condensation tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Goulas and Gokhale studied the kinetics of the coupled dehydrogenation of butanol into butyraldehyde and its subsequent aldol condensation with furfural. 599 The reaction was carried out in the gas phase using a fixed-bed reactor packed with Ni-MgO-Al 2 O 3 as heterogeneous catalyst. The study demonstrated that both dehydrogenation and aldol condensation reactions were catalyzed by the basic sites of the catalyst.…”
Section: Upgrading Of Furansmentioning
confidence: 99%
See 1 more Smart Citation
“…Goulas and Gokhale studied the kinetics of the coupled dehydrogenation of butanol into butyraldehyde and its subsequent aldol condensation with furfural. 599 The reaction was carried out in the gas phase using a fixed-bed reactor packed with Ni-MgO-Al 2 O 3 as heterogeneous catalyst. The study demonstrated that both dehydrogenation and aldol condensation reactions were catalyzed by the basic sites of the catalyst.…”
Section: Upgrading Of Furansmentioning
confidence: 99%
“…The scope of the methodology was extended to single and double aldol condensation with acyclic symmetrical and unsymmetrical ketones as well as cyclic ketones (Table ). Goulas and Gokhale studied the kinetics of the coupled dehydrogenation of butanol into butyraldehyde and its subsequent aldol condensation with furfural . The reaction was carried out in the gas phase using a fixed-bed reactor packed with Ni-MgO-Al 2 O 3 as heterogeneous catalyst.…”
Section: Upgrading Of Furansmentioning
confidence: 99%